Effect of pulsed corticosteroids and tocilizumab on hyperinflammation in COVID-19 patients with acute respiratory distress syndrome - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Objective: To compare the efficacy of pulsed-dose corticosteroids (>= 250 mg methylprednisolone, 3 days) and tocilizumab in treating COVID-19-related hyperinflammation. Methods: This prospective observational study included RT-PCR positive COVID-19 patients with acute respiratory distress syndrome, who were admitted to the COVID-19 Adult Intensive Care Unit of Prof Dr. Murat Dilmener Emergency Hospital (Istanbul, Turkey) between December 1, 2020 and February 28, 2021. Clinical, laboratory and radiological examinations were used to diagnose COVID-19 associated hyperinflammation. Three cohort groups were formed: the pulsed-dose corticosteroids group (250 mg methylprednisolone for 3 days), the tocilizumab group (8 mg/day single dose or 400 mg/day for 2 days), and the combined group (pulsed-dose corticosteroid+tocilizumab). The difference in mortality rates among the groups was compared primarily. The most common cause(s) of death was determined. Furthermore, adverse events (secondary infection, acute kidney injury, arrhythmia, gastrointestinal system bleeding) for 28 days were recorded. Results: A total of 60 patients were included in this study, with 20 patients in each group. There was no statistically significant difference between the 3 groups in mortality rates (55% in the pulsed corticosteroid group, 60% in the tocilizumab group, 50% in the combined group, chi 2=0.404, P=0.817). Infectious causes were found to be the most common cause of mortality in all the three groups, and no difference was found between them (chi 2=0.404, P=0.817). There was also no difference in the development of adverse events such as secondary infection, acute kidney injury, arrhythmia, and gastrointestinal bleeding among the groups (P>0.05). Conclusions: Corticosteroids can be used instead of tocilizumab to treat hyperinflammation in COVID-19 patients with acute respiratory distress syndrome.
Keywords: COVID-19; Acute respiratory distress syndrome; Hyperinflammation; Pulse dose steroid; Tocilizumab; CARE